2007
DOI: 10.5704/moj.0705.007
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Absence of Palmaris Longus in a Multi-racial Population

Abstract: Palmaris longus is a dispensable muscle with a long tendon which is very useful in reconstructive surgery. It is absent 2.8 to 24% of the population depending on the race/ethnicity studied. Four hundred and fifty healthy subjects (equally distributed among Malaysia's 3 major ethnic groups) were clinically examined for the presence or absence of palmaris longus. This tendon was found to be absent unilaterally in 6.4% of study subjects, and bilaterally in 2.9% of study participants. Malays have a high prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 5 publications
1
38
0
Order By: Relevance
“…In nearby populations related historically with Indonesia, Malaysian Malay ethnic group, the rate of PL absence was 11.3%. 17 It was found that the rate of PL absence in Indonesian population was not much different which was 10.4%. However, when compared to other studies in countries far away from Indonesia, it was quite different.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In nearby populations related historically with Indonesia, Malaysian Malay ethnic group, the rate of PL absence was 11.3%. 17 It was found that the rate of PL absence in Indonesian population was not much different which was 10.4%. However, when compared to other studies in countries far away from Indonesia, it was quite different.…”
Section: Discussionmentioning
confidence: 92%
“…In this study they found no significant relationship. 17 Especially for Betawi, even though included in ethnic group according to Central Bureau Of Statistics in 2010, historically this ethnic was a mixture of several ethnic group. The difference between PL absences with ethnicity indicated that the formation of PL in human body was influenced by genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is a slender, fusiform shaped muscle arising from the common flexor origin of the medial epicondyle of the humerus, passing between the flexor carpi radialis and flexor carpi ulnaris muscles, it ends as a slender, flattened tendon passing superficially over the transverse carpal ligament and inserting into the palmar aponeurosis 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the PLT has been reported to be absent in 3.7-50.8% of individuals [1,6,[16][17][18], and in such cases, using the PLT as a landmark will be impossible. This problem can be circumvented by using the distal forearm bony prominences (RSP and USP) as anatomical landmarks for determining the position of the MN, as suggested by our study.…”
Section: Discussionmentioning
confidence: 99%